Physicochemical and Techno-Functional Properties of Dried and Defatted Porcine Liver - Blanca Abril; Eduardo A. Sánchez-Torres; Mònica Toldrà; Jose Benedito; Jose V. García-Pérez (Biomolecules, 2022)
Porcine liver has a high nutritional value and is rich in proteins, minerals, and vitamins, making it an interesting co-product to alleviate the growing global demand for protein. The objective of this study was to analyze how the drying and defatting processes of porcine liver affect the physicochemical and techno-functional properties of its proteins. Two drying temperatures (40 and 70 °C) were studied, and dried samples were defatted using organic solvents. The drying process turned out to be an effective method for the stabilization of the protein fraction; however, when the drying temperature was high (70 °C), greater protein degradation was found compared to drying at a moderate temperature (40 °C). Regarding the defatting stage, it contributed to an improvement in certain techno-functional properties of the liver proteins, such as the foaming capacity (the average of the dried and defatted samples was 397% higher than the dried samples), with the degree of foaming stability in the liver dried at 40 °C and defatted being the highest (13.76 min). Moreover, the emulsifying capacity of the different treatments was not found to vary significantly (p > 0.05). Therefore, the conditions of the drying and defatting processes conducted prior to the extraction of liver proteins must be properly adjusted to maximize the stability, quality, and techno-functional properties of the proteins.